2012
DOI: 10.3109/02713683.2011.647224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on miRNA Expression in Human Y79 Retinoblastoma Cells

Abstract: These observations suggest that curcumin modulate the miRNA expression profile, thereby exerting its anticancer effects on RB cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Interestingly, emerging studies have demonstrated that some herbal product (e.g curcumin, camptothecin, andrographolide and resveratrol etc.) can perform their anti-tumor effects through affecting miRNAs expression [16, 23-25]. However, whether the antitumor effect of baicalein is related to its modulation of miRNA expression in HCC is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, emerging studies have demonstrated that some herbal product (e.g curcumin, camptothecin, andrographolide and resveratrol etc.) can perform their anti-tumor effects through affecting miRNAs expression [16, 23-25]. However, whether the antitumor effect of baicalein is related to its modulation of miRNA expression in HCC is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, emerging studies have demonstrated that Chinese medicinal herbs can exert their anti-tumor effects through targeting miRNAs [15]. For example, curcumin could alter the miRNA expression profile in human retinoblastoma and pancreatic cancer cells, involving some well-known cancer-related miRNAs, such as miR-22, a tumor-suppressor miRNA was upregulated after curcumin treatment [16, 17]. Curcumin also can promote the apoptosis of cancer cells via miR-186, miR-15a and miR-16 and can inhibit the proliferation, invasion and metastasis of cells via miR-21, miR-208 [18-21].…”
Section: Introductionmentioning
confidence: 99%
“…Among the upregulated miRNAs is miR-22, and its overexpression inhibited cell proliferation and migration. The erythoblastic leukemia viral oncogene homolog 3 (Erbb3) was confirmed as its target in the same study [45]. …”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin exerted its inhibitory effect on nasopharyngeal carcinoma (NPC) metastasis through inhibiting expression of miR-125a-5p and subsequently increasing expression of P53. 50 The expression of p53 was associated with cancer aggressiveness correlating with increased grading of invasive cancer front and cancer depth. 51 Bcl-2 was originally identified as a key regulator of apoptosis, but there are increasing evidences that show that Bcl-2 could also promote cancer cell migration and invasion.…”
Section: Curcumin Modulates Mirnas To Restrain Cancer Invasion and Mementioning
confidence: 99%